Chronic rhinosinusitis and endoscopic sinus surgery in children admitted for pulmonary exacerbations of cystic fibrosis. (January 2021) - Wang, Cynthia; Johnson, Romaine; Horani, Sami; Brown, Clarice; Mitchell, Ron; Shah, Gopi
Abstract: Objective: Non-surgical management of chronic rhinosinusitis (CRS) in children with cystic fibrosis (CF) has been increasing over the last decade. This study examines inpatient children with pulmonary exacerbation of CF who were also diagnosed with CRS and underwent endoscopic sinus surgery (ESS). Study design: We used the 2003 to 2016 Kids Inpatient Database to perform a cross-sectional analysis of inpatients (ages 0–21 years) diagnosed with CF and CRS in the United States from 2003 to 2016. Demographics and CF-associated comorbidities were recorded and rates of CRS and ESS in children with CF were examined. Results: 49, 110 children were included in the study. A total of 9334 (19%) were diagnosed with CRS. The average age was 13 (SD 5.9) years; the majority were female (56%), and White (67%). The prevalence of CRS increased from 2003 to 2016 (14%–23%, p < 0.001) while the rate of ESS decreased (20%–11%, p < .001). Patients with CRS that underwent ESS more commonly had CF-associated comorbidities including GI manifestations (15%–25%, p < .001) and liver disease (15%–30%, p < .001). Conclusion: The diagnosis of CRS in children with CF hospitalized for pulmonary exacerbation has increased while ESS has decreased in the last decade. Patients with CRS that underwent ESS more commonly had CF-associated comorbidities. Studies to determine whether children with CF-associated comorbidities are more likely to benefit from ESS are needed. Highlights: The diagnosis of CRS in children with CF who are hospitalized for pulmonary exacerbations has increased. The rate of endoscopic sinus surgery in this population has decreased in the last decade. Patients with CRS that underwent ESS more commonly had CF-associated comorbidities.